Wheat Leaf Diseases and Possibilities of Computer Program Application for Disease Control (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2006)
The main task of integrated plant protection is to reduce usage of pesticides and to address a request of farmers to cut down variable costs for winter wheat growing (including costs of fungicides). A new tool providing these requirements is a Decision support system based on PC program. Validation trials of PC-P Diseases were carried out in collaboration with Danish Institute of Agricultural Sciences in 1999-2002 in different regions in Latvia. Comparisons were made among standard treatments with full dose of Tango Super (epoxiconazole 84 g l-1, fenpropimorf 250 g l-1) in GS 51-55, split doses in GS 37-39 and GS 51-55 and treatment according to PC-P recommendation. Tan spot (Drechslera tritici-repentis), leaf blotch (Septoria tritici) and mildew (Blumeria graminis) were the most important diseases in this period. The results of trials showed that average doses of fungicide were decreased according to PC-P Diseases recommendations, treatment frequency index fluctuated from 0.2-1.02. Reduced doses of fungicides showed the same efficiency of diseases control as standard doses. Level of additional yield was similar in comparison with variants where standard doses were used.